2011
DOI: 10.1001/archinternmed.2011.34
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Divide in Adoption and Use of a Personal Health Record

Abstract: Background: Personal health records (PHRs) offer the potential to improve the patient experience and the quality of patient care. However, the "digital divide," the population-level gap in Internet and computer access, may prevent certain groups from accessing the PHR.Methods: We conducted a cross-sectional analysis of a PHR within a northeastern health system. We compared adopters (ie, those activating a PHR account online) with nonadopters (ie, those who see a physician offering the PHR but do not activate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
259
2
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(275 citation statements)
references
References 13 publications
11
259
2
3
Order By: Relevance
“…As demonstrated in previous studies, 7,8 we found significant demographic differences in PHR users and non-users, including such factors as lower age and higher incomes. Given these differences, it was not surprising to find better unadjusted diabetes quality measure profiles in PHR users.…”
Section: Discussionsupporting
confidence: 83%
“…As demonstrated in previous studies, 7,8 we found significant demographic differences in PHR users and non-users, including such factors as lower age and higher incomes. Given these differences, it was not surprising to find better unadjusted diabetes quality measure profiles in PHR users.…”
Section: Discussionsupporting
confidence: 83%
“…Covariates for adjustment were chosen according to clinical significance and possible effect on portal adoption (1,(3)(4)(5)(6)(7)(8)10,11,(13)(14)(15)29,31,33,34,36,(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). Sociodemographic variables were age, sex, race, marital status, insurance status, neighborhood median household income, tobacco use, and follow-up duration.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We sought to address this gap by examining portal use, including secular trends, in universityaffiliated general nephrology clinics. Given previous literature indicating that underserved groups are less likely to use EHR portals (32)(33)(34)(35)(36), we hypothesized that race, neighborhood median household income, and insurance status would be associated with portal use and of particular concern in view of documented CKD disparities in these groups (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In addition, we believed that BP control, a key modifiable outcome that affects CKD progression, would depend on patient adherence, self-monitoring, and patient-provider communication.…”
Section: Introductionmentioning
confidence: 99%
“…A strength of this study is its focus on a linguistically diverse patient population with multiple chronic conditions receiving care in an integrated group practice setting. Research has shown that minorities in general are less likely to use online health-related patient SMRs or portals, [12][13][14] and our results suggest that speaking a non-English language is associated with low use of remote refill systems, including the Internet.…”
Section: Discussionmentioning
confidence: 53%
“…11 African Americans and Latinos are less likely to use an online SMR system that has options to request medication refills. [12][13][14] In view of the lack of reliable data on patient language use in most health care systems, and the enormous challenges of conducting cross-cultural and multi-lingual research, to our knowledge, there are no studies examining the use of the medication refill functionality of SMRs by linguistically diverse populations. This study addresses this gap by investigating the use of Internet and telephone medication refill systems integrated within an SMR among an ethnically diverse sample of insured patients with chronic illnesses, and investigates differences in use between patients with limited English proficiency (LEP) and English-proficient (EP) patients.…”
Section: Introductionmentioning
confidence: 99%